Los Intentos de Deslegitimación del Derecho al Aborto en Puerto Rico - Colón, Alice E.; Dávila, Ana Luisa; Fernós, María Dolores; Vicente, Esther (Puerto Rico Health Sciences Journal, 2016)
see manuscript